Indications of suppression of excited Υ states in Pb-Pb collisions at √(s(NN))=2.76 TeV. - Chatrchyan, S; Khachatryan, V; Sirunyan, A; Tumasyan, A; Adam, W; Bergauer, T; Dragicevic, M; Erö, J; Fabjan, C; Friedl, M; Frühwirth, R; Ghete, V; et al. (2011)
A comparison of the relative yields of Υ resonances in the μ(+)μ(-) decay channel in Pb-Pb and pp collisions at a center-of-mass energy per nucleon pair of 2.76 TeV is performed with data collected with the CMS detector at the LHC. Using muons of transverse momentum above 4  GeV/c and pseudorapidity below 2.4, the double ratio of the Υ(2S) and Υ(3S) excited states to the Υ(1S) ground state in Pb-Pb and pp collisions, [Υ(2S+3S)/Υ(1S)](Pb-Pb)/[Υ(2S+3S)/Υ(1S)](pp), is found to be 0.31(-0.15)(+0.19)(stat)±0.03(syst). The probability to obtain the measured value, or lower, if the true double ratio is unity, is calculated to be less than 1%.